Frequency of the ICD 10 diagnosis called "problems related to inadequate social skills" in children, according to age and sex in a physical therapy and rehabilitation polyclinic, Villa el Salvador. Lima Peru - Guevara-Tirado, Alberto (2022)
Objective. To evaluate the frequency of the ICD-10 diagnosis called "problems related to inadequate social skills" in children according to age and sex in a physical therapy and rehabilitation polyclinic in the district of Villa el Salvador in Lima, Peru. Materials and methods. Observational, descriptive, retrospective and cross-sectional study based on the compilation of data concerning the diagnosis CIE-10 code Z73.4 “problems related to inadequate social skills” of 188 patients of both sexes in a parochial polyclinic of physical therapy and rehabilitation located in the district of Villa el Salvador during the months of January 2021 to July 2022. The study variables were: sex, age and diagnosis Z73.4. I have a validated collection form. The sample was the total of the objective population which was 218 patients, patients with a history of neurodevelopmental disorders such as autism and ADHD, as well as organic disorders such as epilepsy, were excluded. For the statistical analysis, the program SPSS statistics 25 was used. Descriptive statistics and tables were used. Results. With a total of 218 patients, it was found that 87.16% of the patients evaluated were male, compared to the female gender, which accounted for only 12.8%. Those who attended the physical therapy and rehabilitation center for the assessment and treatment concerning problems related to social skills, in general, were students at the pre-school stage with a 57.79%. Conclusion. There is a high frequency of care for problems related to inadequate social skills in boys than in girls.